Радиофизические исследования в Украине - Костенко, А.А.; Носич, А.И.; Яковенко, В.М. (Радиофизика и радиоастрономия, 2004)
В работе представлена история радиофизических исследований в Украине с конца XIX столетия до настоящего времени. Отмечена роль крупнейших ученых-радиофизиков в основании научных школ и формировании научных направлений. В контексте социально-политических преобразований и экономических реформ показаны основные этапы развития радиофизики в вузах, академических и отраслевых институтах Украины. Ukraine’s efforts in radio physics are shown historically covering the period from the end of the 19th century until present. The contribution of masterminds in the field to foundation and shaping of research areas and schools is emphasized. The major steps in the development of radio physics in Ukrainian universities and research institutes, including those of the National Academy of Sciences, are traced against the background of socio-political and economic reforms.